Non-coherent cohesive texts Lucky's soliloquy in Beckett's Waiting for Godot - Abu-Ayyash, Emad A. S. (2021)
—The present mixed-methods study investigated the readiness of teachers and adult learners at a vocational centre in the United Arab Emirates to implement a negotiated English syllabus. The study addressed two main questions: 1) are teachers and learners at the Vocational Training Centre ready to implement a negotiated syllabus? And 2) does the negotiated syllabus implementation lead to improvement in learners’ motivation? Results showed the significant potential of a negotiated syllabus in enhancing learners’ motivation by making them part of the decision-makers’ circle regarding the components of an intended English syllabus. On the other hand, learners, teachers and management systems face challenges that must first be overcome to succeed in implementing negotiated syllabi. The findings of this study support the value of involving learners in classroom decisions, which is expected to make them feel responsible for their learning.